The Effect of Shear on the Properties of Rigid PVC (Journal of Engineering, 2011)
The rheological and fusion behavior of polyvinyl chloride (PVC) compounds plays a dominant role inthe processing operations and in the development of physical properties in the processed material. Acomprehensive study was made in this work to evaluate the effect of shear and thermal history on stability, mechanical and rheological properties of rigid PVC compounds. Different samples of Rigid Poly vinyl chloride including dry blend powder, granules, and bottles molded from both were examined. A study was also made on recycled RPVC where 25% of reclaimed material was continuously blended with fresh dry blend and processed for 15 cycles. Results showed that compaction of the PVC material took place in the brabender plastograph at constant temperature and shear stress. Correlations were given to explain results concerning residual stability and rheological behavior. Furthermore, it was seen that elongation and tensile impact are dependent on shear history.